A comparative study of the alterations of cardiovascular aptitude in old aged women practicing walking exercises in Alvarenga, MG - Martins Pousas, Fabiana; Santos Rodrigues, Andressa; Araújo Duarte, Israel; Salustiano Bispo, André (O Mundo da Saúde, 2007)
The present study analyzed the alterations in the cardiovascular aptitude in aged walking exercises practitioners in Alvarenga, MG. Research subjects were ten old aged sedentary women with ages between 60 and 70 years, divided in two groups: a control and a research group. Each group had 5 members, and they were evaluated through a battery of tests proposed by Fernandes Filho (2003). Training with intervention was followed only in the research group, consisting of a 10-week walking exercise program. Through evaluating cardiovascular parameters, it was verified in pre-and post-test that statistically significant results had been reached for the research group when compared with the control group, and we identified mainly a VO2 maximo increase, and a reduction of arterial pressure and cardiac frequency at rest, a result that evidences that walking exercises promote beneficial alterations in cardiovascular aptitude in aged women practitioners.